Ginseng-based carbon dots inhibit the growth of squamous cancer cells by increasing ferroptosis - Wang, Zilin; Han, Jing; Guo, Zhiyong; Wu, Hao; Liu, Yige; Wang, Wenying; Zhang, Chenping; Liu, Jiannan (Frontiers in Oncology, 2023)
Background Recent studies indicated that Ginseng potentiate cancer treatments. Ginseng-based carbon dots (GCDs) might possess properties to kill cancer cells and inhibit malignant tumor development and invasion. This study aimed to prepare GCDs, examine their effects on cancer cell growth and invasion, and explore the mechanisms involved. Methods GCDs were synthesized, purified, and characterized. Cells were cultured with GCDs and were tested for growth, invasiveness, and wound healing. RNA was extracted for transcriptomics analysis. Protein expression was evaluated using western blot and immunohistochemistry. Mice were injected with cancer cells and treated with PBS or GCDs. Tumor volume was evaluated. Results GCDs were successfully synthesized and purified. The solution was yellow under sunlight and fluorescent blue under ultraviolet light. Electron microscopy showed GCDs with a uniform shape without apparent aggregation and an average diameter of about 4 nm. GCDs inhibited Cal-27, SCC-25, and SCC-7 cancer cell growth at concentrations of >250-300 μg/mL, while GCDs inhibited the non-cancerous HaCaT cells at concentrations >400 μg/mL. Immunofluorescence showed that GCDs could enter the cells. Transcriptomics revealed 552 downregulated mRNAs and 338 upregulated ones, including mRNAs involved in the oxidative phosphorylation and ferroptosis pathways. GCDs induced the ferroptosis of cancer cells, as shown by decreased GPX-4 and increased COX-2. GCDs decreased cell invasion and migration. In vivo, GCDs decreased tumor growth without apparent organ toxicity and promoted CD4+ T cell infiltration in the tumor. Conclusion GCDs appear to possess anticancer properties by increasing ferroptosis, resulting in cancer cell growth inhibition in vitro and in vivo.